Makna Naga Dalam Iklan Marjan 2023 “Baruna Sang Penjaga Samudera” - Syafruddin Pohan; Rima Ivana (Student Scientific Creativity Journal, 2023)
Advertising is one of the mass communication media in the form of visual, audio, writing, or a combination of audio-visual. As with any communication in general, every advertisement must have an implicit or explicit meaning contained therein which is addressed to the public. Marajan as one of the syrup products in Indonesia, often makes advertisements that are full of meaning with attractive packaging. The purpose of this study is to find out the meaning of the dragon in Marjan 2023 advertisement "Baruna Sang Guardian of the Ocean" by using a qualitative descriptive theory approach and Roland Barthes' Semiotics theory which interprets something based on the denotative and connotative meanings of signifiers, signifieds and signs that exist in an object. The results of this study indicate that the dragon in the ad refers to a social disaster caused by humans who often throw plastic waste into the ocean.